ANALISIS PENGARUH SUKU BUNGA, INFLASI DAN PDB TERHADAP JUMLAH PERMINTAAN KREDIT PERBANKAN DI INDONESIA TAHUN 2009-2019 - Riski Nur Arianti; Muhammad Faisal Abdullah (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
Credit demand has an important role and affects economic growth. The demand for credit can be influenced by various factors, both internal and external. This study aims to see how much influence the macroeconomic factors have on the demand for bank credit in Indonesia. The data used in this research is secondary data in the form of quarterly data for the 2009-2019 period. The results show that simultaneously there is a significant positive effect contributed by the variable rate of inflation, exchange rate, and Gross Domestic Product on banking stock prices in Indonesia with a Prob value. F-statistic 0.0000 <0.05. The partial results show that interest rates have a significant negative effect on banking stock prices, inflation has a negative and insignificant effect on bank credit demand, while Gross Domestic Product has a significant positive effect on bank credit demand in Indonesia